2001
DOI: 10.1080/03075070120043206
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Information and Communication Technologies in a University Learning Environment

Abstract: This article reports three related studies which investigate how undergraduates use and think about information and communication technologies (ICT) in the context of learning at university. Data were obtained via questionnaires, computer diary records and focus group discussions. The studies were intended to help universities decide how to incorporate ICT into student learning, how the cost of equipment should be shared between students and institutions, and how university provision should be organised to bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
0
8
0
4
Order By: Relevance
“…However, the need to distribute education to different sites in an equitable and comparable way requires systems, structures and processes to effectively support distribution. Relatedly, the actual work of being a medical teacher has also changed, and now involves a variety of essential, but somewhat invisible tasks, that differentiate this work from what it might have been historically, not unlike in the broader context of higher education (Blin & Munro, 2008;Breen et al, 2001;Kirkwood & Price, 2013;Unwin, 2007).…”
Section: Teaching Facultymentioning
confidence: 99%
“…However, the need to distribute education to different sites in an equitable and comparable way requires systems, structures and processes to effectively support distribution. Relatedly, the actual work of being a medical teacher has also changed, and now involves a variety of essential, but somewhat invisible tasks, that differentiate this work from what it might have been historically, not unlike in the broader context of higher education (Blin & Munro, 2008;Breen et al, 2001;Kirkwood & Price, 2013;Unwin, 2007).…”
Section: Teaching Facultymentioning
confidence: 99%
“…Code-to-sentence matches should occur in at least 80 per cent of cases to claim high reliability. The themes extracted from the case study example are reported in detail in Breen et al (2001) and Lindsay et al (2002).…”
Section: Analysing Focus-group Datamentioning
confidence: 99%
“…Participants in the case study were undergraduate students who were asked to take part in some institutional research that was intended to inform university policy on the provision of its IT resources. The case study was published in Studies in Higher Education (Breen et al, 2001) and has been selected as an example for several reasons.…”
Section: A Case Studymentioning
confidence: 99%
“…Christie et al (2002) argued that ICTs drastically changing both workplaces and the educational site (Christie et al, 2002). This was previously debated by Breen et al (2001) and Wenglinski (1998) who also alleged that the growth in the educational use of ICTs does prove that these modern technologies can facilitate education (Breen et al, 2001;Wenglinski, 1998).…”
Section: Ict In Higher Education Augments Online-learningmentioning
confidence: 93%